2000
DOI: 10.1134/1.1331142
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of a low-pressure glow discharge in air in large-diameter discharge tubes: I. conditions for the normal regime of a glow discharge

Abstract: -The initiation and characteristics of a low-pressure glow discharge in air in large-diameter discharge tubes are studied. A deviation from the Paschen law is observed: the breakdown curves U dc ( pL ) shift toward the higher values of U dc and pL as the interelectrode distance L increases. It is shown that the normal regime of a glow discharge is accompanied by gas ionization in the anode sheath. This takes place only for pL values lying to the right of the inflection point in the breakdown curve. The cathode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 18 publications
4
33
0
Order By: Relevance
“…The toroidal structure of the plasma at low currents was also reported in the experiments by Lisovskiy et al [70]. The electron temperature is found to be nearly uniform in the bulk plasma region with a value of about 12,000 K (∼ 1 eV) and rises sharply in the cathode sheath regions adjacent to the cathode surface and the lower part of the quartz dielectric wall (the extended cathode surface).…”
Section: Y (M)supporting
confidence: 52%
See 1 more Smart Citation
“…The toroidal structure of the plasma at low currents was also reported in the experiments by Lisovskiy et al [70]. The electron temperature is found to be nearly uniform in the bulk plasma region with a value of about 12,000 K (∼ 1 eV) and rises sharply in the cathode sheath regions adjacent to the cathode surface and the lower part of the quartz dielectric wall (the extended cathode surface).…”
Section: Y (M)supporting
confidence: 52%
“…The experiments were performed by Lisovskiy et al [70] in a parallelplate direct-current glow discharge environment. The discharge geometry and the computational mesh used for the simulations are shown in Fig.…”
Section: Air Plasma Model Validation Resultsmentioning
confidence: 99%
“…The temperature is determined from the slope of the linear region of lnðI electron Þ vs V Bias plot near the floating potential, 29,30 where I electron represents the electronic part of the probe current and V Bias represents the probe bias voltage. The plasma density is determined from the ion current using the results of the modified TALBOT and CHOU model.…”
Section: Experimental Set Upmentioning
confidence: 99%
“…They also observed the deviations from the Paschen law. Lisovskiy et al [8][9][10][11] studied the low pressure gas breakdown in a number of gases with different electrode materials in cylindrical tubes with different inter-electrode distance values L and discharge chamber radius values R (in the range L/R 3). They demonstrated that the gas breakdown in dc electric field was described by a modified law…”
Section: Introductionmentioning
confidence: 99%